The Association between Health Workforce and Health Outcomes: A Cross-Country Econometric Study - Liu, Jinlin; Eggleston, Karen (Social indicators research, 2022)
This study investigates the strength and significance of the associations of health workforce with multiple health outcomes and COVID-19 excess deaths across countries, using the latest WHO dataset. Multiple log-linear regression analyses, counterfactual scenarios analyses, and Pearson correlation analyses were performed. The average density of health workforce and the average levels of health outcomes were strongly associated with country income level. A higher density of the health workforce, especially the aggregate density of skilled health workers and density of nursing and midwifery personnel, was significantly associated with better levels of several health outcomes, including maternal mortality ratio, under-five mortality rate, infant mortality rate, and neonatal mortality rate, and was significantly correlated with a lower level of COVID-19 excess deaths per 100 K people, though not robust to weighting by population. The low density of the health workforce, especially in relatively low-income countries, can be a major barrier to improving these health outcomes and achieving health-related SDGs; however, improving the density of the health workforce alone is far from enough to achieve these goals. Our study suggests that investment in health workforce should be an integral part of strategies to achieve health-related SDGs, and achieving non-health SDGs related to poverty alleviation and expansion of female education are complementary to achieving both sets of goals, especially for those low- and middle-income countries. In light of the strains on the health workforce during the current COVID-19 pandemic, more attention should be paid to health workforce to strengthen health system resilience and long-term improvement in health outcomes. The online version contains supplementary material available at 10.1007/s11205-022-02910-z.